Integrated Multi-Method Probes as a Research Method in Cognitive Systems Engineering. (September 2017) - Murphy, Taylor; Balkin, Asher; Rayo, Michael; Woods, D. D.; Zelik, Dan
The continued development of Cognitive Systems Engineering (CSE) as both an academic discipline and as a field of practice requires constant and continuous reconsideration of the types of techniques used in research. Currently, all CSE research is conducted in one of three research settings: experimental/spartan laboratory studies, simulation/staged world studies, and in-situ observational techniques. We argue that rather than representing three discrete categories of techniques, these archetypes are instead points which exist on a continuum. By navigating the trade-offs between fidelity/external-validity and the control of variability, new hybrid research forms will emerge. These integrated multi-method probes which borrow from all three classic archetypes create more rigorous studies which provide both high quality data and contextual information. The authors present an exploration of the development of expertise of intelligence analysts involved in the ALFAA program as an example of this research tool set.